Parental emotional support, self-efficacy, and mental health problems among adolescents in Hong Kong: a moderated mediation approach - Qian, Mengting; Jin, Rui; Lu, Chunping; Zhao, Mingren (Frontiers in Psychiatry, 2024)
Introduction Early signs of mental health issues may develop into severe mental illnesses over time. The influence of parental emotional support on adolescent mental health problems is well acknowledged. However, prior research has predominantly focused on psychological symptoms, often neglecting the somatic symptoms associated with mental health. Additionally, there has been insufficient exploration of the mediating role of self-efficacy and the relationship between socioeconomic status (SES) and adolescent mental health, particularly within the context of Hong Kong. Methods Using data from 3,613 adolescents aged 15 years from 109 schools in Hong Kong who participated in the Programme for International Student Assessment 2018, this study explored the relationship between parental emotional support and two dimensions of adolescent mental health symptoms (psychological and somatic symptoms), and the mediating effect of self-efficacy and the moderating role of SES. Results We found that parental emotional support significantly reduced psychological and somatic symptoms, primarily by enhancing self-efficacy. MoreovSES moderated these relationships, with the impact of parental emotional support on psychological symptoms being more pronounced among adolescents from lower SES backgrounds. Discussion This study deepens the understanding of the mechanisms underlying adolescent mental health in Hong Kong. By highlighting the importance of parental emotional support and self-efficacy, as well as the moderating effect of SES, the findings offer valuable insights for effective interventions aimed at improving adolescent mental health.